An XFEM-VCCT coupled approach for modeling mode I fatigue delamination in composite laminates under high cycle loading. (15th May 2021) - Teimouri, Farhad; Heidari-Rarani, Mohammad; Haji Aboutalebi, Farhad
Highlights: Extended finite element method (XFEM) and virtual crack closure technique (VCCT) are coupled to each other. Fatigue delamination in composites is simulated via XFEM-VCCT approach. Direct cyclic method is evaluated for high cycle fatigue delamination growth. XFEM-VCCT shows high accuracy and low computational time in 3D-solid FE models. Challenges ahead of VCCT and XFEM-VCCT are discussed. Abstract: In this study, virtual crack closure technique (VCCT) and extended finite element method (XFEM) are coupled to each other as XFEM-VCCT approach to simulate mode I fatigue delamination growth in composites, employing the direct cyclic method in Abaqus. Both two-dimensional plane strain and three-dimensional finite element models under force and displacement control are considered. Numerical simulation results are compared with the existed experimental test data for double cantilever beam (DCB) specimens and validated. Finally, challenges ahead of VCCT and XFEM-VCCT are discussed in detail and the appropriate method for modeling fatigue delamination growth in laminated composites under high cycle loading is suggested. It is found that simulation of the DCB fatigue delamination via the displacement control loading leads to more accurate results in comparison to the force control. VCCT was found as a suitable method for simulation of fatigue delamination growth in 2D and 3D-shell models. While XFEM-VCCT shows high accuracy and low computational time in 3D-solid finite element models. The key conclusion is that the XFEM-VCCT coupled approach is independent of time increment, whereas the time increment is more effective on the results of VCCT analysis, and it affects the run-time significantly.